A Regression Analysis of Generation Y Female Students’ Perceptions on Social Risk, Buying Behaviour and Apparel Store Choice - Mokoena, Bakae Aubrey; Maziriri, Eugine Tafadzwa (Journal of Economics and Behavioral Studies, 2017)
In the present post-modern era, Generation Y female students are faced with a discerning process of selecting the optimum apparel retail store to be loyal to and from which to buy clothing products. Therefore, the active store choice decision is conceptualized as the difficulty of determining someplace and when and where to shop. The main objective of the study was to examine the relationship between social risk, buying behavior and store choice within the apparel retail industry. The study is positioned within a post-positivism quantitative paradigm and adopts a cross-sectional survey approach collecting data from 400 conveniently selected university students. Scale purification was done through pre-testing and pilot testing. Through multiple regression analysis, the results show that social risk and buying behavior significantly influences retail store choice in an apparel retail setting. The findings indicated that there is a positive and significant association between perceived social risk, buying behavior and retail store choice. Based on the outcomes of the study, recommendations were suggested to retail managers to develop retailing strategies that charm the female Generation Y consumers. In addition, limitations and future research directions are referred to.